“Determinants of rural household saving participation: A case study of Libokemkem District, North-west Ethiopia” - Melsew Nibret Mazengiya; Girmachew Seraw; Birhanu Melesse; Tesfaye Belete (Cogent Economics & Finance)
Saving is an important factor in households’ welfare in developing countries. However, most studies have focused on urban areas and at the macroeconomic level. Consequently, such studies mask the reality of rural households, which constitute a large proportion in Ethiopia. Hence, this study aims at analyzing the factors that influence the probability of saving participation at the household level in the Libokemkem District. We employed a systematic random sampling technique to select a total of 157 household heads in three kebeles in Libokemkem District, Ethiopia. We used structured questionnaires to collect data from the sampled households. We then analyzed the data using a logistic regression model. The results of the study show that family size, farm land, education status, credit access and frequency of extension contact are the determinant factors for saving participation among rural households. We recommend that the Ethiopian Ministry of Economic and Finance should strengthen the existing credit services and create awareness campaigns for the communities to enhance rural saving participation.